Incidence and Histopathology of Hepatocellular Carcinoma in Iraqi Patients - Dhafer Jawad (Central Asian Journal of Medical and Natural Science, 2023)
This study aimed to Know the Incidence and Histopathology of hepatocellular carcinoma in Iraqi patients. A study was conducted on 41 patients diagnosed with hepatocellular carcinoma (HCC) between February 2022 and March 2023. The study cohort consisted of 32 male and 9 female patients with different ages. The study participants were obtained from medical and surgical units across multiple hospitals and subsequently referred to a specialized pathological laboratory located in the Baghdad Province. Liver biopsy can be performed through various methods such as Trucut needle biopsy, Chiba needle biopsy directly on liver tissue or under ultrasound guidance, or open liver biopsy through diagnostic laparoscopy or explorative laparotomy. Histological slides were done and stained with H&E stain. The findings of the present study or data analysis indicate a discrepancy in disease rates between genders, with males exhibiting higher rates compared to females. The current findings exhibited that age group (51-60 years) were highly diseased than other groups. On histopathology, the growth patterns of tumoral hepatocytes can be classified into three distinct types: trabecular, acinar or pseudoglandular, and compact or solid. The trabecular pattern is distinguished by the disposition of hepatocytes in plates of diverse thickness, which are demarcated by vascular spaces known as sinusoids. The acinar or pseudoglandular configuration is distinguished by the expansion of canaliculi between neoplastic cells, resembling glandular structures, with luminal spaces that may harbour bile, or the central deterioration of trabeculae, with luminal spaces predominantly occupied by fibrin. The compact or solid pattern comprises of dense trabeculae that are compressed into a compact entity. In conclusion, males were more diseased than females especially at age 50-61 years and histopathology can aid in diagnosis and differentiate HCC from other liver diseases.